MULTIMEDIA TECHNOLOGIES IN THE TRAINING OF STUDENTS OF HIGHER EDUCATION INSTITUTIONS IN UKRAINE FOR ANIMATION ACTIVITIES IN THE RECREATION AND WELLNESS SECTOR (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This article examines the development of animation competencies among future tourism professionals in the recreational and wellness sector through the implementation of multimedia technologies. A theoretical model was developed and empirically validated to enhance professional training efficiency through computer-based tools. The research emphasizes the role of interactive presentations, video content, virtual and augmented reality applications, and specialized software in the educational process. The study surveyed 330 students from Ukrainian higher education institutions regarding multimedia technology integration in tourism education. Results demonstrated that students most effectively acquired skills in designing animation programs incorporating health fitness components (46.55%) and sports activities (45.12%), while showing lower proficiency in organizing sports animation and wellness centre activities (22.14%). A survey of 72 higher education instructors revealed varying pedagogical approaches: 39.57% prioritize preparation for animation activities in recreation and wellness; 46.05% implement regular computer-based assessments; 41.72% utilize business simulations; 41.41% conduct master classes; and 48.75% organize quest-based learning activities. The data indicated that 16.79% of instructors emphasize fitness and wellness animation programming, while only 4.67% focus on entertainment-based animation. Furthermore, 48.65% evaluate animation competencies through event organization (competitions, performances, festivals, carnivals, and theatrical productions); 33.82% prioritize experience in music-based animation programs; and 57.66% advocate for practical training in various professional settings, including hotel and restaurant complexes, wellness centres, sanatoriums, children's camps, resorts, and transportation facilities. The findings suggest that multimedia technology integration enhances creativity, communication skills, and collaborative abilities—competencies essential for animation activities in tourism. This research demonstrates that incorporating digital tools into tourism education effectively addresses contemporary tourism industry demands and professional requirements.